Burocracias diplomáticas em ditaduras entrelaçadas: Brasil e Argentina - Vanuza Nunes Pereira (2018)
This dissertation, elaborated as part of the collective project of the Centro de Estudos sobre Justiça de Transição, explores more deeply one of its key elements: the right to truth. It research the characteristics of the Brazilian diplomatic bureaucracy, in a comparative analysis with that of Argentina, using Operation Condor as the factual and methodological phenomenon for investigation, mainly between 1976 and 1980, in order to unveil the antagonisms and the similarities between the two bureaucratic instances during their respective military regimes. It is believed that the role played by the Brazilian diplomatic bureaucracy through its official discourse of neutrality, served as clothing of legality to legitimize and hide the performance of the military regime in repressive transnational operations. In analyzing the issue in comparison with the Argentinean Chancellery, it is possible to observe that the activities were not the result of a momentary institutional rupture, but of continued actions, which, because of the conservative profile and the high degree of preservation of the Brazilian dictatorship, prevented, and even after redemocratization continued to prevent, the accomplishment of the right to truth.